2011
DOI: 10.3109/15412555.2011.586659
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Burden of Depression/Anxiety in Chronic Obstructive Pulmonary Disease Patients within a Managed Care Population

Abstract: In the COPD population, patients with depression/anxiety have significantly higher risk of COPD exacerbations and annual all-cause and COPD-related costs than patients without these co-morbidities. These findings may have therapeutic implications and seem worthy of further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 27 publications
0
67
1
2
Order By: Relevance
“…Patients with a CCS congestive heart failure or "cardiac dysrhythmia/arrest/ventricular fi brillation" comorbidity grouping were 1.29 (95% CI, 1.22-1.37) and 1.20 (95% CI, 1.12-1.28) times as likely to be subsequently admitted to the hospital, respectively. These estimates are slightly lower than those from Dalal et al 24 for patients with cardiovascular disease comorbidities-they were 1.62 (95% CI, 1.40-1.88) times as likely to be admit ted to the hospital. Patients with "mixed" COPD/asthma diagnoses have been shown to be less likely to have defi ne a COPD-related visit when a COPD diagnostic code appeared in the fi rst or second position.…”
Section: Comorbiditiescontrasting
confidence: 50%
“…Patients with a CCS congestive heart failure or "cardiac dysrhythmia/arrest/ventricular fi brillation" comorbidity grouping were 1.29 (95% CI, 1.22-1.37) and 1.20 (95% CI, 1.12-1.28) times as likely to be subsequently admitted to the hospital, respectively. These estimates are slightly lower than those from Dalal et al 24 for patients with cardiovascular disease comorbidities-they were 1.62 (95% CI, 1.40-1.88) times as likely to be admit ted to the hospital. Patients with "mixed" COPD/asthma diagnoses have been shown to be less likely to have defi ne a COPD-related visit when a COPD diagnostic code appeared in the fi rst or second position.…”
Section: Comorbiditiescontrasting
confidence: 50%
“…The result is often increased risk of exacerbation, [7][8][9][10][11] hospital admission, 8,9 and early death. 2,3,9,11,12 For patients with COPD with coexisting anxiety and in particular panic disorder, misinterpretation of the cause of dyspnea may lead to heightened arousal, followed by additional negative cognitions not found in those without panic attacks.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The true prevalence of these conditions in patients with COPD varies and depends upon the measurement tool used for their assessment. [4][5][6] Studies examining the effect of psychological disorders in patients with COPD have shown that such patients have more visits to the primary care physician and ED, 7,8 greater risk of exacerbation [7][8][9][10][11] and hospitalization, 8,9 as well as longer hospital stays 2,9 and higher risk of death, 2,3,9,11,12 than patients with COPD in good mental health.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Współistnienie podwyższonego reagowania lękowego związanego z występowaniem duszności stanowi niezależny czynnik ryzyka wystąpienia zaostrzenia wymagającego hospitalizacji [213] oraz znacząco zwiększa koszty leczenia w porównaniu z chorymi na POChP bez współistnienia depresji i lęku [214]. Ponadto u chorych z objawami depresji i podwyższonym lękiem rzadziej uzyskuje się satysfakcjonujące efekty leczenia zaostrzenia.…”
Section: Wsparcie Psychologiczneunclassified